aprilmeens82
aprilmeens82
02-04-2020
Mathematics
contestada
Find −6+(−9)−6+(−9).
Respuesta :
yzeng808
yzeng808
02-04-2020
Answer:
-30
Step-by-step explanation:
This can be rewritten as
-6-9-6-9 = -(6+9+6+9) = -30
Answer Link
hmmiwonder
hmmiwonder
02-04-2020
Answer:
69
Step-by-step explanation:
nice
nice
nice
nice
nice
Answer Link
VER TODAS LAS RESPUESTAS ( 74+ )
ACCESS MORE
Otras preguntas
Note: the 2 in the answers are exponents In a video game, a ball moving at 0.6 meter/second collides with a wall. After the collision, the velocity of the ball
Find the possible value or values of n in the quadratic equation 2n2 – 7n + 6 = 0. A. n = −2, n = −32 B. n = 32, n = 2 C. n = 6, n = 0 D. n =
Birds are believed to have evolved from dinosaurs. Which of the statements best validates the about fact? It has been published in various medical journals Bir
In what ways was the Ottoman Empire influenced both by previous Islam empires and the Byzantine Empire?
What is 4(2x+5)=-49+61 simplified
If you are charged in a crash with injuries and are driving a motorcycle, you are _______________ for any bodily injuries and property damage to others. Poss
What is most likely the reason that the United States is no longer the largest producer of steel? A. Failure to adopt modern steel production techniques. B. Low
Hi! Can you please help me with this question? If you can please show the steps on how you got the answer. There is a picture to go with it. Thank you! 1. The a
What is a reasonable estimate for the circumference of a circle with a radius of 12 inches? A. C≈36in. B. C≈72in. C. C≈144in. D. C≈432in.
In trapezoid ABCD with bases AB and DC , diagonals intersect at point O. Prove that: AO/BO = AC/BD = CO/DO